Evaluation Of 3d Bimetric Maxıllary Distalizing Arches And Cervical Headgears As Per Their Effects On Dentofacial Structures - Ayşe Tuba Altuğ; Dilek Erdem (Galenos Yayinevi, 2004)
In this study, the dentofacial effects of 3D bimetric maxillary distalizing system, which is an intraoral molar distalization technique, and cervical headgear, which is an extraoral distalization technique in cases requiring maksillary molar distalization, were evaluated. Another purpose of the study was to determine the effectiveness of the fully bonded and banded mandibular dental arches in increasing the anchorage of the mandibular dental arch for the intermaxillary class II elastics used in the 3D bimetric maxillary distalization group. The most significant differences between the two maxillary first molar distalization techniques were observed within the mandibular dental arches. In the 3D bimetric maxillary distalization group, the fully bonding and banding of the mandibular dental arches was not effective enough for increasing the mandibular anchorage.